PENGARUH KOMPOSISI PLASTIK POLIPROPILENA DAN PARTIKEL BATANG PISANG BARANGAN TERHADAP KUALITAS PAPAN PLASTIK - Winda Martogi Situmeang; Tito Sucipto; Apri Heri Iswanto (Program studi Kehutanan USU, 2016)
Banana trunk is agricultural waste which is potentially as one of the solutions to be used as a material utilization berlignoselulosa products such as plastic boards. The purpose of this study was to evaluate the effect of the composition of the plastic PP and banana stem particles to quality plastic board and determine the best composition for the physical and mechanical properties of plastic boards. Making plastic boards using a variation of the composition of polypropylene plastic (PP) and banana stem particles are 50:50, 60:40, 70:30 and 80:20. Mixing materials is done by using an extruder machine and compression board sheets using hot compressed at a temperature of 170 0C pressure of 25 kgf/cm2 for 10 minutes. The sample size of 25 cm x 25 cm x 1 cm3 with a target density of 0.7 g/cm3. Data analysis was carried out using a completely randomized design (CRD) with three replications. The results of this study compared with SNI 03-2105-2006. The density value of from 0.52 to 0.73 g/cm3, 1.67 to 4.32% moisture content, water absorption in immersion 2 hours from 1.88 to 11.41%, and 24 hours immersion 5.38 to 28,48%, thickness swelling at 2 hours of immersion from 0.21 to 0.41%, and 24 hours from 0.43 to 0.69%, MOE 2710-6170 kgf/cm2, MOR 50.72 to 128.49 kgf/cm2, IB 1.11 to 2.94 kgf/cm2. Variations in the composition of the plastic polypropylene (PP) and banana stem particles affect the physical and mechanical properties of plastic boards. Treatment on the composition of 70:30 is the best treatment for physical and mechanical properties of plastic boards.Keywords: banana stems, plastic polypropylene, physical and mechanical properties, wood polymer composite